Implementasi Teknologi Augmented Reality dalam Pengajaran Bahasa Asing: Studi Eksperimental - Arshel Rizky Saputra; Ananda Wahyu Lorena (BADAN PENERBIT STIEPARI PRESS, 2021)
This research aims to explore the effectiveness of using Augmented Reality (AR) technology in foreign language teaching. AR technology offers a more interactive and immersive learning experience, which can help students understand and master foreign languages ​​more effectively. This research used an experimental method involving 60 students who were divided into two groups, namely the experimental group which used AR and the control group which used conventional methods. The results showed that students who used AR technology experienced significant improvements in speaking, listening and vocabulary skills compared to the control group. These results indicate that the implementation of AR in foreign language teaching can be an effective strategy in improving students' language skills.